2016
DOI: 10.1016/j.ijppaw.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

First description of Onchocerca jakutensis (Nematoda: Filarioidea) in red deer ( Cervus elaphus ) in Switzerland

Abstract: Twenty-seven species of the genus Onchocerca (Nematoda; Filarioidea) can cause a vector-borne parasitic disease called onchocercosis. Most Onchocerca species infect wild and domestic ungulates or the dog, and one species causes river blindness in humans mainly in tropical Africa. The European red deer (Cervus e. elaphus) is host to four species, which are transmitted by blackflies (simuliids) or biting midges (ceratopogonids). Two species, Onchocerca flexuosa and Onchocerca jakutensis, produce subcutaneous nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…(Filarioidea; Onchocercidae) nematodes were associated with greenish discolouration and oedema of subcutaneous tissues in cervids ( Laaksonen et al, 2017 ) and domestic species ( Solismaa et al, 2008 ). Adult Onchocerca worms are localised free or in nodules in subcutaneous tissues and produce microfilariae in these sites ( Bosch et al, 2016 ; Boijsen et al, 2017 ). Dead or dying adult worms or microfilariae may trigger inflammatory reactions characterized by infiltration of eosinophilic granulocytes and multifocal nodular lymphoplasmacytic aggregations around them, followed by calcification and fibrosis ( Solismaa et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Filarioidea; Onchocercidae) nematodes were associated with greenish discolouration and oedema of subcutaneous tissues in cervids ( Laaksonen et al, 2017 ) and domestic species ( Solismaa et al, 2008 ). Adult Onchocerca worms are localised free or in nodules in subcutaneous tissues and produce microfilariae in these sites ( Bosch et al, 2016 ; Boijsen et al, 2017 ). Dead or dying adult worms or microfilariae may trigger inflammatory reactions characterized by infiltration of eosinophilic granulocytes and multifocal nodular lymphoplasmacytic aggregations around them, followed by calcification and fibrosis ( Solismaa et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four Onchocerca species were described in red deer in Central Europe (i.e. O. skrjabini and O. garmsi free in subcutaneous tissues, and O. flexuosa and O. jakutensis in subcutaneous nodules) ( Bosch et al, 2016 ; Boijsen et al, 2017 ), and O. jakutensis infection was reported in 26% of red deer of the Grisons region ( Bosch et al, 2016 ). Although the occurrence of Onchocerca spp.…”
Section: Discussionmentioning
confidence: 99%
“…flexuosa , Wedl, 1856; O . jakutensis , Guvanov, 1964) [911], wolves and dogs ( O . lupi , Rodonaja, 1967) [12].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, we report the first case of O. jakutensis ocular infection. Onchocerca jakutensis is a common parasite of red deer detected in the Russian Federation [9], Switzerland [10], Italy [1], Germany [11], the Czech Republic [12], the Slovak Republic [12] and Poland [9]. A study by Demiaszkiewicz [13] has shown that O. jakutensis parasitize red deer in several regions of Poland, among others, in the south-west part, where patient described in the present report lives.…”
Section: Discussionmentioning
confidence: 56%